HUBUNGAN PENDIDIKAN DAN HUKUM DALAM MENSEJAHTERAKAN MANUSIA - Kallang, Abdul (Institut Agama Islam Negeri (IAIN) Bone, 2017)
This paper discusses the relationship between education and law in the welfare of humans. So, the discussion is related to the educational situation that should be applied as well as the law that is appropriately enforced, not only many rules, but the rules are not enforced. All teachers must understand and understand that the concept or method of education is very different now. The point is we must understand, practice with the present context. Likewise, the law must be applied in the context of the present. In everyday life, humans must walk, not stop, turn to the left and to the right, sometimes backward, but must continue to advance in achieving what he wants by paying attention to the situation around one of them is to pay attention to those related to education and law. Both epistemologically, axiologically and ontologically. what I mean here is what is the definition of education and also law? What is the basis of the importance of education and law? And c. What is the relationship between education and law in the welfare of humans.